Fatiguing Trunk Flexor Exercise Decreases Pain Sensitivity in Postpartum Women - Deering, Rita (Front Physiol, 2019)
BACKGROUND: Low back pain (LBP) is common in the general population and among postpartum women. Abdominal muscle exercise is often used to treat LBP, but it is unknown if fatiguing abdominal muscle exercise can produce exercise-induced hypoalgesia (EIH). OBJECTIVES: To assess pressure pain thresholds (PPTs) at rest and following fatiguing trunk flexor exercise (EIH) in (1) nulligravid and postpartum women to evaluate the impact of pregnancy and childbirth and (2) nulligravid women and men to examine sex differences. METHODS: Seventy healthy adults (31 postpartum women, 23 nulligravid women, 16 men) participated. Postpartum and nulligravid women were tested twice (16–18 weeks apart) to identify changes in EIH with postpartum recovery. PPTs were measured at the nailbed and superior rectus abdominis before and after exercise to investigate systemic and local EIH, respectively. Rectus abdominis muscle thickness was assessed with ultrasound. RESULTS: Postpartum women reported lower PPTs than nulligravid women at the abdomen (p < 0.05) whereas postpartum women had lower PPTs at the nailbed during the first session only. Men reported higher nailbed PPTs (p = 0.047) and similar PPTs at the abdomen than women (p = 0.294). All groups demonstrated EIH at the abdomen (p < 0.05). Systemic EIH was absent in postpartum and nulligravid women (p > 0.05), while men demonstrated hyperalgesia. Local EIH was positively associated with muscle thickness for men and women, which was not significant at the second timepoint. LIMITATIONS: Acute exercise response may not reflect changes that occur with exercise training. CONCLUSION: Fatiguing trunk flexor exercise produced local EIH for all groups including postpartum and nulligravid women. Clinically, trunk exercises may be useful for acute pain relief for clinical populations that are characterized by pain and/or weakness in the abdominal region muscles in populations with abdominal pain syndromes.